the effect of qualitative competitive volleyball exercises on improving motor satisfaction - لواتي , عبد السلام; مداسي , لطفي (Journal of Sport Science Technology and Physical Activities, 2025)
The Object of the study aims to identify the effect of exercise on improving motor satisfaction , for this purpose, we used the method experimental On a sample composed of 32 pupil Chosen as intentionality, and for data collection, we used a tool questionnaire After collecting the results and having treated them statistically, we conclude exercise has an effect on improving motor satisfaction On this basis, the study recommended interest in physical education to improve psychological skills